THE MODERNIZATION OF MADRASAH IN THE PERSPECTIVE OF A. MALIK FADJAR - Muh Idris; Evra Willya (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to explore and deeply analyze the intellectual construction of A. Malik Fadjar regarding the modernization of the madrasah as an effort toward inclusive and progressive Islamic educational reconstruction in Indonesia. Specifically, the study identifies his strategic steps in eliminating the intellectual dichotomy and reforming institutional management in response to the challenges of globalization. This study is a qualitative research employing a library research design with a focus on biographical and intellectual study (studi tokoh). Since the primary object of investigation is the intellectual thought of A. Malik Fadjar regarding the modernization of the madrasah, the approach utilized is the social history of Islamic educational thinking. This approach was selected because the researcher intends not only to dissect the texts literally but also to explore the dialectic between the figure's thoughts and the surrounding social, political, and cultural contexts during the inception of those ideas. The results demonstrate that madrasah modernization, from A. Malik Fadjar's perspective, is a paradigmatic transformation rooted in the concept of Tawhid as the convergence point for integrating science (dhikr) and technology (fikr). He positioned the madrasah no longer as a "second-class institution" but as a competitive general school with a distinctive Islamic character. This transformation is realized through three primary policies: accommodating the autonomous aspirations of the Ummah, strengthening the mastery of science and civic skills, and responding to the demands of the information era through professional management. Despite critiques regarding his managerial style which relied heavily on trust his vision proved capable of bridging pesantren traditions with the demands of Western modernity. Practically, this research emphasizes the importance of shifting madrasah management patterns from traditional-conventional models toward professional and adaptive governance that meets local and global labor market needs. These findings provide a foundation for madrasah administrators to maintain religious identity (tafaqquh fiddin) while continuously innovating through integrative curricula. The originality of this study lies in its analytical focus, which shifts the discourse on A. Malik Fadjar’s thought from a general-philosophical level to specific operational steps within the context of madrasah reconstruction in Indonesia. This research offers a new paradigm for developing the madrasah as an institution that is intellectually competitive while remaining steadfast in its foundation of Islamic morality,